The Association of Glucose Control with Circulating Levels of Red Blood Cell-Derived Vesicles in Type 2 Diabetes Mellitus Patients with Atrial Fibrillation - Berezin, A. A.; Obradovic, Z.; Kopp, K.; Berezina, T. A.; Lichtenauer, M.; Wernly, B.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2023)
Hyperglycemia is a trigger for structural alteration of red blood cells (RBCs) and their ability to release extracellular vesicles (EVs). The aim of the study was to elucidate whether glucose control in T2DM patients with concomitant HF and AF affects a circulating number of RBC-derived EVs. We prospectively included 417 T2DM patients with HF, 51 of them had atrial fibrillation and 25 healthy volunteers and 30 T2DM non-HF individuals. Clinical assessment, echocardiography examination and biomarker measures were performed at the baseline of the study. RBC-derived EVs were determined as CD235a+ PS+ particles by flow cytometry. NT-proBNP levels were measured by ELISA. AF patients with glycosylated hemoglobin (HbA1c) < 6.9% had lower levels of CD235a+ PS+ RBC-derived vesicles than those with HbA1c 7.0%. There were no significant differences in number of CD235a+ PS+ RBC-derived vesicles between patients in entire cohort and in non-AF sub-cohort with HbA1c < 6.9% and HbA1c 7.0%, respectively. Multivariate linear regression yielded that CD235a+ PS+ RBC-derived vesicles 545 particles in L (OR = 1.06; 95% CI = 1.01–1.11, p = 0.044) independently predicted HbA1c 7.0%. Elevated levels of CD235a+ PS+ RBC-derived EVs independently predicted poor glycaemia control in T2DM patients with HF and AF.
Keywords: diabetes mellitus; heart failure; red blood cells; extracellular vesicles; hyperglycemia